2015
DOI: 10.1515/bot-2014-0075
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of nine species of Martensia (Delesseriaceae, Rhodophyta) reported from Korea based on morphology and molecular analyses

Abstract: Previous taxonomic studies reported that nine species of Martensia (i.e., Martensia albida, Martensia australis, Martensia bibarii, Martensia elegans, Martensia flammifolia, Martensia fragilis, Martensia jejuensis, Martensia projecta, and Martensia palmata) occur on the Korean coast. Our recent Martensia collections from various localities in Korea contain many specimens with a huge range of morphological variation and are difficult to classify into the named species. In this study, we analyzed DNA sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…1) are not closely allied with either material from Sri Lanka (the type locality for the species), or material known from any other location ( Fig. 1; Kang et al, 2015), and thus represent an undescribed species (most of the specimens are represented by the species described here as M. tsudae). The taxonomic situation for specimens previously referred to as M. flabelliformis (lineage 2, and some specimens in lineage 5, Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1) are not closely allied with either material from Sri Lanka (the type locality for the species), or material known from any other location ( Fig. 1; Kang et al, 2015), and thus represent an undescribed species (most of the specimens are represented by the species described here as M. tsudae). The taxonomic situation for specimens previously referred to as M. flabelliformis (lineage 2, and some specimens in lineage 5, Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Portions of the COI (cytochrome oxidase subunit I, 658 bp) barcoding region were amplified using the GazF2 and GazR2 primers (Saunders, 2005;Lane et al, 2007). Similarly, portions of the rbcL gene (ribulose 1,5-bisphosphate carboxylase/oxygenase large subunit; 1442 bp) were sequenced and assembled by amplifying two overlapping fragments using the primers rbcLF7 (Gavio & Fredericq, 2002) and rbcLJNR1 (Kang & Kim, 2013) for the first fragment, and rbcLF762 and rbcLR1442 (Kim et al, 2010) for the second fragment, as suggested by Kang et al (2015). For most Martensia DNA extracts, a 1:100 dilution was required for successful amplification and sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Morphological plasticity, intraspecific variation in form due to environmental differences, makes identifying specimens difficult [33][34][35][36][37]. Similarly, different species with convergent morphologies are difficult to distinguish [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…These dilemmas are not confined to any particular taxon or region, but to various macroalgae worldwide. Molecular methods using DNA sequencing have improved the delimitation of species with similar morphologies, as well as species with morphological plasticity in various taxonomic groups [33,37,[41][42][43]. In particular, chloroplast-encoded rbcL sequences are useful for species-level delimitation among members of the Delesseriaceae (e.g., [37,41,42,[44][45][46]), and a large quantity of verified rbcL sequences from previous studies is available from GenBank [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular techniques applied in other red algae have led to the discovery of multiple cryptic species that were previously classified as a single species (Yang and Kim 2018, Nauer et al 2019, Yang et al 2021a, Preuss et al 2022. Simultaneously, multiple species defined by morphological traits were found to belong to a singular species using molecular data (Kang et al 2015). Therefore, DNA-based phylo-…”
Section: Genetic Diversity and Phylogeographic Structure Using The Co...mentioning
confidence: 99%